MR safety watchdog for active catheters: Wireless impedance control with real‐time feedback. Issue 2 (21st January 2020) - Özen, Ali Caglar; Silemek, Berk; Lottner, Thomas; Atalar, Ergin; Bock, Michael
Abstract : Purpose: To dynamically minimize radiofrequency (RF)‐induced heating of an active catheter through an automatic change of the termination impedance. Methods: A prototype wireless module was designed that modifies the input impedance of an active catheter to keep the temperature rise during MRI below a threshold, ΔTmax . The wireless module (MR safety watchdog; MRsWD) measures the local temperature at the catheter tip using either a built‐in thermistor or external data from a fiber‐optical thermometer. It automatically changes the catheter input impedance until the temperature rise during MRI is minimized. If ΔTmax is exceeded, RF transmission is blocked by a feedback system. Results: The thermistor and fiber‐optical thermometer provided consistent temperature data in a phantom experiment. During MRI, the MRsWD was able to reduce the maximum temperature rise by 25% when operated in real‐time feedback mode. Conclusion: This study demonstrates the technical feasibility of an MRsWD as an alternative or complementary approach to reduce RF‐induced heating of active interventional devices. The automatic MRsWD can reduce heating using direct temperature measurements at the tip of the catheter. Given that temperature measurements are intrinsically slow, for a clinical implementation, a faster feedback parameter would be required such as the RF currents along the catheter or scattered electric fields at the tip.